Implications of false alarms in dynamic games on cyber-security. (April 2023) - Han, Kookyoung; Choi, Jin Hyuk
Abstract: Cyber-threats including computer viruses, data breaches, and denial-of-service attacks have become increasingly prevalent and need to be handled effectively. Imperfect prevention of cyber-attacks inevitably results in false alarms from the defense system. We consider a dynamic game in which a defender operating an intrusion detection system is penalized for false alarms. By characterizing the equilibrium of the game, we search for the implications of false alarms under various circumstances. Specifically, we consider the cyber-insurance market, operational risk, and government intervention. Our model shows that both demand and supply of cyber-insurance can be low, which explains the underdevelopment of the cyber-insurance market. The analysis of an extended model with operational risk shows that reducing the operational risk decreases the cyber-risks but increases the false alarm rate. Regarding government intervention, we suggest a simple policy that achieves a socially optimal outcome. Highlights: We consider a dynamic game in which a defender is penalized for false alarms. Both demand and supply of cyber-insurance can be low. High operational risk makes the defender to wait longer for more convincing evidence. Reducing operational risk decreases defender's costs but increases false alarm costs. We suggest a simple government policy that achieves socially optimal outcome.